Two-dimensional ACI type perovskite thin film, solar cell and preparation method of two-dimensional ACI type perovskite thin film
By spin-coating guanidine-based derivative solution on the electron transport layer of two-dimensional ACI perovskite solar cells, the problems of buried interface defects and poor contact are solved, the photoelectric conversion efficiency is improved, and higher charge transmission and photoelectric performance are achieved.
Patent Information
- Application Number
- CN202411317540.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-31
AI Technical Summary
Two-dimensional ACI perovskite solar cells have defects at the buried interface and poor contact between the electron transport layer and the perovskite absorbing layer, which affects the photoelectric conversion efficiency.
Spin coat guanidine derivative solution on the electron transport layer to form a buried interface layer modified by guanidine derivatives, and spin coat guanidine derivatives on the perovskite absorbing layer, using guanidine groups to interact with the perovskite absorbing layer to produce a relationship , modify the TiO2 surface, inhibit the formation of iodine vacancies, promote the growth of perovskite crystals, and enhance the crystal quality of the film.
It effectively reduces the defect state density, improves the charge extraction rate, enhances the photoelectric conversion efficiency, solves the problems of poor contact between the electron transport layer and the perovskite absorption layer and the buried interface, and improves the photoelectric performance of the device.
Smart Images

Figure CN119233740A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of perovskite solar cells, and specifically to a two-dimensional ACI-type perovskite solar cell with a modifier added at a buried interface and a preparation method thereof. Background Art
[0002] Perovskite solar cells have attracted extensive attention in the field of new energy due to their advantages such as high absorption coefficient, adjustable band gap and simple preparation method. Although three-dimensional perovskite solar cells are the most widely studied, their material structure is unstable and they are very sensitive to factors such as moisture, oxygen, heat and ultraviolet radiation. The prepared devices have poor stability in actual application, which has become the main challenge for their further commercialization.
[0003] Related studies have confirmed that the A-position organic small molecules (methylamine ions MA) in the three-dimensional perovskite structure + or formamidinium ion FA + ) easily reacts with water, thus destroying the perovskite structure and causing it to lose its original photoelectric properties. This is the main reason for the instability of perovskite solar cells.
[0004] As an extension material of three-dimensional perovskite, two-dimensional perovskite mainly uses hydrophobic organic spacer cations with larger ionic radius to replace A-site cations, destroying the symmetry of the perovskite cube (exceeding the Goldschmidt Tolerance Factor for forming the perovskite structure) to form a stacked structure of organic spacer cation layers and perovskite layers. Compared with the A-site cations of three-dimensional perovskite solar cells, the organic spacer layer molecules of two-dimensional perovskite solar cells have higher hydrophobicity, larger size structure and lower volatility, so they have more advantages in thermal, chemical and environmental stability.
[0005] According to the different organic spacer cations, the two-dimensional perovskite structure can be divided into
[0006] Ruddlesden–Popper (RP), Dion–Jacobson (DJ), and
[0007] Alternating-cation Interlayer (ACI) type. At present, RP-type and DJ-type perovskite solar cells have been widely studied, while the research on ACI-type perovskite solar cells is relatively limited. ACI-type perovskite solar cells use smaller and more symmetrical guanidine ions as organic spacer cations. Compared with RP-type and DJ-type perovskites, they have smaller structural distortion, more regular cation stacking, shorter inorganic interlayer spacing, smaller band gap and lower exciton binding energy. However, in the preparation process of ACI-type perovskite solar cells, there are defects such as iodine vacancies and uncoordinated lead ions in the buried interface. At the same time, the poor contact between the perovskite absorption layer and the electron (hole) transport layer affects the transmission of electrons between the interface layers, thereby affecting the further improvement of the photoelectric conversion efficiency of perovskite solar cells.
[0008] In order to solve the above problems, researchers use MACl as a bulk additive, and also use imidazole iodide, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, etc. as surface treatment to passivate the top interface defects of the perovskite film and improve the performance of perovskite solar cells. Although these strategies have made some progress in improving the efficiency of ACI-type perovskite solar cells, there is still a gap in the photoelectric conversion efficiency with three-dimensional perovskite solar cells. Summary of the invention
[0009] In view of this, the present invention provides a two-dimensional ACI-type perovskite film, a solar cell and a preparation method thereof, which solve the problems of poor contact between the electron transport layer and the perovskite absorption layer of the current two-dimensional perovskite solar cell and defects in the buried interface.
[0010] To achieve the above-mentioned object of the invention, in a first aspect, the two-dimensional ACI-type perovskite film has a molecular structure as follows:
[0011] A'A n B n X 3n+1 ;
[0012] Where: A' is a guanidine ion, A is one or more of methylamine, formamidine or cesium ion, and B is Pb 2+ and / or Sn 2+ , X is Cl - Br - ,I - One or more of, n is the number of inorganic layers.
[0013] In the present disclosure and possible embodiments, the film is composed of a buried interface layer coated on an electron transport layer and a two-dimensional perovskite light absorbing layer coated on the buried interface layer;
[0014] The buried interface layer is a spin-coated film of a guanidine derivative solution.
[0015] In the present disclosure and possible embodiments, the guanidine derivative is p-guanidinobenzonitrile or dicyandiamide;
[0016] The guanidine derivative solution is obtained by dissolving the p-guanidine benzonitrile or the dicyandiamide in N,N-dimethylformamide, isopropanol or ethyl acetate.
[0017] In the present disclosure and possible embodiments, the concentration of the guanidine derivative solution is 1-10 mg / ml.
[0018] In a second aspect, the two-dimensional ACI-type perovskite solar cell comprises:
[0019] An electron transport layer on the surface of a conductive substrate;
[0020] A buried interface layer and a perovskite light absorption layer are arranged on the electron transport layer;
[0021] In the first aspect, the two-dimensional ACI-type perovskite film serves as the buried interface layer and the perovskite light-absorbing layer.
[0022] In the present disclosure and possible embodiments, a hole transport layer and a top electrode are sequentially disposed on the perovskite light absorbing layer.
[0023] In the present disclosure and possible embodiments, the conductive substrate is a transparent conductive substrate, and the transparent conductive substrate is a glass substrate, a quartz substrate, a PET plastic substrate, a PEN plastic substrate or a PI plastic substrate; and / or,
[0024] The electron transport material of the electron transport layer is TiO2, SnO2 or ZnO.
[0025] In the present disclosure and possible embodiments, the electron transport layer is formed of an indium tin oxide, a fluorine-doped tin dioxide or a grid silver film prepared on the conductive substrate.
[0026] In a third aspect, the method for preparing the two-dimensional ACI-type perovskite solar cell according to the second aspect comprises:
[0027] After preparing the electron transport layer on the conductive substrate, the substrate was transferred to a glove box filled with N2, and the guanidine derivative solution was spin-coated on the electron transport layer, annealed on a hot plate at 80-100°C for 5-10 minutes, and allowed to cool to room temperature to obtain an electron transport layer modified with the guanidine derivative.
[0028] In the present disclosure and possible embodiments, after spin coating the two-dimensional perovskite light absorbing layer on the guanidine derivative-modified electron transport layer, a Spiro-OMeTAD hole transport layer is spin coated on the perovskite light absorbing layer, and an Ag top electrode is evaporated on the hole transport layer.
[0029] The present invention has the beneficial effects:
[0030] The two-dimensional ACI type perovskite solar cell disclosed in the present invention adds a guanidine derivative additive to the electron transport layer. First, the functional groups (guanidine, cyanide, carboxyl, sulfonic acid, etc.) present in the additive can modify the surface of the TiO2 electron transport layer, and the additive molecules are used to reduce the accumulation of charges at the interface between the electron transport layer and the perovskite film light absorption layer, so that the electron transport layer and the perovskite film layer can achieve the purpose of synergistic passivation on both sides, thereby passivating the deep trap state on the surface; the functional groups with lone pairs of electrons can react with Pb 2+ Lewis acid-base reaction occurs, and the coordination with Sn4+ in the substrate such as SnO2 can effectively suppress the hysteresis phenomenon of forward scanning and reverse scanning, greatly reduce the defect state density, effectively increase the charge extraction rate, and thus enhance the photoelectric conversion efficiency of the device; in addition, the guanidine group present in the molecule can produce a certain interaction with the guanidine ion in the perovskite absorption layer, thereby promoting the growth of perovskite crystals in a better orientation and promoting the transmission of charge in the perovskite absorption layer; at the same time, the functional group forms hydrogen bonds with the halogen element ions in the perovskite, which can effectively suppress the generation of iodine vacancies and further improve the photoelectric performance of the device; more importantly, the guanidine group can serve as a nucleation site to achieve the directional induced growth of ACI-type perovskite film and improve the crystallization quality of the film; therefore, the guanidine derivative additive provided by the present disclosure plays the role of electron transmission channel and adhesive between the electron transport layer and the perovskite absorption layer, which can effectively solve the problems of poor contact between the electron transport layer and the perovskite absorption layer and the defects of the buried interface. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings herein are incorporated into the specification and constitute a part of the specification. These drawings illustrate embodiments consistent with the present disclosure and are used to illustrate the technical solutions of the present disclosure together with the specification.
[0032] Figure 1 This is a flow chart of a method for preparing a two-dimensional ACI-type perovskite solar cell according to an embodiment of the present disclosure;
[0033] Figure 2 Schematic diagram of the structure of a two-dimensional ACI-type perovskite solar cell;
[0034] Wherein: 1-top electrode, 2-electron transport layer, 3-perovskite film layer, 4-electron transport layer, 5-transparent conductive substrate;
[0035] Figure 3-1 , 3-2 It is the structure diagram of guanidine derivative molecules (p-guanidine benzonitrile, dicyandiamide);
[0036] Figure 4 It is a JV curve diagram of the two-dimensional ACI type perovskite solar cell of the embodiment of the present disclosure and the comparative example;
[0037] Figure 5 XRD diagram of the two-dimensional ACI-type perovskite thin film layer of the embodiment and comparative example of the present disclosure;
[0038] Figure 6-1 , 6-2 , 6-3, 6-4, 6-5, and 6-6 are SEM images of the upper interfaces of the two-dimensional ACI-type perovskite films of the embodiments of the present disclosure and the comparative examples, respectively;
[0039] Figure 7-1 , 7-2 7-3 are SEM images of the lower interface of the two-dimensional ACI-type perovskite film of the embodiment of the present disclosure and the comparative example, respectively;
[0040] Figure 8-1 , 8-2 8-3 are space charge limited current diagrams of two-dimensional ACI type perovskite solar cells of the embodiment of the present disclosure and the comparative example, respectively;
[0041] Fig. 9 1 is a dark current density-voltage curve of the two-dimensional ACI-type perovskite solar cell of the embodiment of the present disclosure and the comparative example. DETAILED DESCRIPTION
[0042] The present disclosure is described below based on embodiments and comparative examples, but it is worth noting that the present disclosure is not limited to these embodiments. In the detailed description of the present disclosure below, some specific details are described in detail. However, for the parts that are not described in detail, those skilled in the art can also fully understand the present disclosure.
[0043] Furthermore, unless the context clearly requires otherwise, throughout the specification and claims, the words "include," "comprises," and similar words should be interpreted in an inclusive sense rather than an exclusive or exhaustive sense; that is, in the sense of "including but not limited to."
[0044] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0045] The present invention discloses a method for preparing a two-dimensional ACI-type perovskite solar cell in various embodiments, such as Figure 1 As shown, the specific steps are as follows:
[0046] 1. Prepare an electron transport layer on a transparent conductive substrate.
[0047] In each embodiment of the present disclosure, the transparent conductive substrate is a glass substrate, a quartz substrate, a PET plastic substrate, a PEN plastic substrate or a PI plastic substrate; indium tin oxide, fluorine-doped tin dioxide or a grid silver film is prepared on the transparent conductive substrate as a conductive layer; the electron transport material is TiO2, SnO2 or ZnO.
[0048] 2. Spin-coat the buried interface layer on the electron transport layer.
[0049] In each embodiment of the present disclosure, the additive is dissolved in N,N-dimethylformamide or isopropanol in a nitrogen glove box to form an additive solution, and then the additive solution is spin-coated on the electron transport layer, annealed on a 100°C hot stage for 5 minutes, and allowed to cool to room temperature to obtain the buried interface layer, thereby adding the additive to the electron transport layer.
[0050] The additive is p-guanidinobenzonitrile or dicyandiamide; the concentration of the additive solution is 1-10 mg / ml.
[0051] 3. Spin-coat a two-dimensional perovskite light-absorbing layer on the electron transport layer.
[0052] (1) Preparation of quasi-two-dimensional ACI-type perovskite precursor solution:
[0053] In each embodiment of the present disclosure, the specific preparation steps are: lead iodide, methylamine iodide, and guanidine iodide are dissolved in N, N-dimethylformamide and dimethyl sulfoxide (the volume ratio of N, N-dimethylformamide and dimethyl sulfoxide is 10:1) in a ratio of 5:5:1. In addition, 10 mg of methylamine chloride is added per milliliter of solution and dissolved in N, N-dimethylformamide and dimethyl sulfoxide (the volume ratio of N, N-dimethylformamide and dimethyl sulfoxide is 10:1), and stirred for about 12 hours to obtain a perovskite precursor solution with a concentration of 1.2 M.
[0054] (2) Spin-coating the perovskite precursor solution on the electron transport layer to obtain a perovskite light absorbing layer:
[0055] The molecular structure of the perovskite light absorbing layer is A'A n B n X 3n+1 , wherein A' is a guanidine ion, A is one or more of MA or FA or cesium ion, and B is Pb 2+ and / or Sn 2+ , X is Cl - Br - ,I - One or more of, n is the number of inorganic layers.
[0056] The specific operation method of spin coating is: spin at a speed of 500 rpm for 3 seconds, 4000 rpm for 60 seconds, and in the last 45 seconds before the end of spin coating, drop 300 μL of anti-solvent ethyl acetate on the spin-coated film, and anneal the spin-coated film with the anti-solvent added on a hot stage at 150°C for 20 minutes in an environment with a relative humidity of 30%-40% to obtain a perovskite light-absorbing layer. The perovskite light-absorbing layer and the buried interface layer constitute a perovskite film.
[0057] 4. Prepare a hole transport layer on the perovskite light-absorbing layer.
[0058] 5. Prepare the top electrode on the hole transport layer to obtain a two-dimensional ACI-type perovskite solar cell.
[0059] Comparative Example
[0060] The two-dimensional ACI type perovskite solar cell is prepared by the existing method, and the specific steps are as follows:
[0061] 1. Prepare an electron transport layer on a transparent conductive substrate.
[0062] Fluorine-doped tin dioxide thin film conductive glass (FTO) conductive glass was continuously ultrasonically washed in deionized water, acetone and ethanol for 15 minutes, then dried under nitrogen conditions, treated with ultraviolet / ozone for 20 to 30 minutes; and its back and edge were adhered with high-temperature tape.
[0063] Titanium tetrachloride and water were mixed in an ice bath at a volume ratio of 1:0.0225 and stirred for ten minutes. The substrate was placed in a titanium tetrachloride aqueous solution and deposited at 70°C for 1 hour. After the deposition was completed, the substrate surface was cleaned with water and ethanol respectively, and annealed on a 100°C hot stage for 1 hour to form an electron transport layer on the FTO conductive glass. After annealing, it was treated with UV-ozone for 15 minutes and then transferred to a glove box filled with N2.
[0064] 2. Prepare two-dimensional ACI-type perovskite precursor solution.
[0065] In an inert gas atmosphere, guanidine iodide, methylammonium iodide, and lead iodide were added to a mixed solvent of N,N-dimethylformamide and dimethyl sulfoxide (the volume ratio of N,N-dimethylformamide and dimethyl sulfoxide was 10:1) in a molar ratio of 1:5:5, and stirred at 60°C for 12 hours to obtain a perovskite precursor solution with a concentration of 1.2 M.
[0066] 3. Prepare a perovskite light absorbing layer on the electron transport layer.
[0067] The perovskite precursor solution is spin-coated on the electron transport layer; the specific spin-coating method is: after rotating at a speed of 500 r / min for 3 seconds, it is rotated at a speed of 4000 r / min for 60 seconds, and within 45 seconds before the end of spin coating, 300 μL of anti-solvent ethyl acetate is dropped on the spin-coated film, and the spin-coated film is annealed on a hot stage at 150°C for 20 minutes under environmental conditions of relative humidity of 30%-40%, to obtain the perovskite film and perovskite light absorbing layer of this comparative example.
[0068] 4. Prepare the hole transport layer and top electrode in sequence on the perovskite light-absorbing layer.
[0069] In an inert gas atmosphere, 520 mg of lithium bis(trifluoromethanesulfonyl)imide was weighed and dissolved in 1 mL of anhydrous acetonitrile to prepare a lithium bis(trifluoromethanesulfonyl)imide solution; 90 mg of Spiro-OMeTAD (2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene) was dissolved in 1 mL of chlorobenzene, and then 36 μL of tributyl phosphate solution and 20 μL of lithium bis(trifluoromethanesulfonyl)imide solution were added; 35 μL of Spiro-OMeTAD precursor solution was drawn with a pipette, the speed was set to 3000 r / min, the acceleration was set to 1000 r / min, and the time was set to 30 s, and the hole transport material was spin-coated on the perovskite film to prepare a hole transport layer, the hole transport layer was Spiro-OMeTAD, and its thickness was about 100 nm; at a vacuum degree of 1×10 -5 Under the conditions of , metal Ag is evaporated on the hole transport layer at a speed of 0.1 to 0.5 A per second to form a 100 nm Ag electrode to obtain a two-dimensional ACI type perovskite solar cell of this comparative example, whose structure is as follows Figure 2 shown.
[0070] The JV curve test of the perovskite solar cell of this comparative example is performed to obtain the energy conversion efficiency of the perovskite solar cell of this comparative example. Figure 4 Control in.
[0071] The perovskite film of this comparative example was subjected to XRD test, and the results are shown in Figure 5 Control in.
[0072] The perovskite film of this comparative example was tested by scanning electron microscope. Figure 6-1 , 6-4 .
[0073] Figure 7-1 , 7-2 7-3 are SEM images of the lower interface of the two-dimensional ACI perovskite film of the embodiment of the present disclosure and the comparative example, and the specific results are shown in Figure 7-1 .
[0074] The perovskite solar cell (FTO / TiO2 / perovskite absorber layer / PCBM / Ag) of this comparative example was tested for space charge limited current. The specific results are shown in Figure 8-1 , where V TFL is the full trap limit voltage, according to V TFL The formula V TFL =eN trap L 2 / 2ε0εCalculate the defect state density N trap .
[0075] The dark current density-voltage curve of the perovskite solar cell of this comparative example was tested, and the specific results are shown in Fig. 9 Control in order to detect its leakage current.
[0076] Example 1
[0077] According to the method of the present invention, a method for preparing a two-dimensional ACI type perovskite solar cell with a guanidine benzonitrile additive is prepared, such as Figure 1 As shown, the specific steps are as follows:
[0078] 1. Prepare an electron transport layer on a transparent conductive substrate.
[0079] The electron transport layer was prepared in the same manner as in the comparative example.
[0080] 2. Spin-coat p-guanidine benzonitrile on the electron transport layer.
[0081] The molecular structure of p-guanidinobenzonitrile is as follows Figure 3-1 As shown, p-guanidinobenzonitrile is dissolved in N,N-dimethylformamide in a nitrogen glove box to form a p-guanidinobenzonitrile solution, and then the p-guanidinobenzonitrile solution is spin-coated on the electron transport layer, annealed on a 100° C. hot stage for 5 minutes, and placed at room temperature to obtain a buried interface layer, through which the p-guanidinobenzonitrile additive is added to the electron transport layer. The concentration of the p-guanidinobenzonitrile solution is 6 mg / ml.
[0082] 3. Prepare two-dimensional ACI-type perovskite precursor solution.
[0083] The perovskite film and the perovskite light absorbing layer were prepared in the same manner as in the comparative example.
[0084] 4. Prepare a perovskite light absorbing layer on the electron transport layer.
[0085] The perovskite light absorbing layer was prepared in the same manner as in the comparative example.
[0086] 5. A hole transport layer and a top electrode are sequentially prepared on the perovskite light-absorbing layer to obtain a solar cell.
[0087] The hole transport layer and the top electrode are prepared by the same method as in the comparative example to obtain the two-dimensional ACI type perovskite solar cell of this embodiment 1, whose structure is as follows: Figure 2 shown.
[0088] The JV curve test of the perovskite solar cell of this embodiment 1 is performed to obtain the energy conversion efficiency of the perovskite solar cell of this embodiment 1. The result is as follows: Figure 4 By comparing the BG group with the Control group, it was found that the energy conversion efficiency of the perovskite solar cell with the addition of guanidine benzonitrile additive was improved.
[0089] The perovskite film of Example 1 was subjected to XRD test, and the results are as follows: Figure 5 By comparing the BG group with the Control group of the comparative example, it was found that the peak intensity corresponding to the perovskite with the addition of p-guanidine benzonitrile additive was improved compared with the Control group. Therefore, the perovskite with the addition of p-guanidine benzonitrile additive has better crystallinity.
[0090] The perovskite film of Example 1 was tested by scanning electron microscope, and the results are as follows: Figure 6-2 , 6-5 , to characterize the morphological changes of perovskite films. Figure 6-2 , Figure 6-5 It can be concluded that the grains of the perovskite film with the addition of guanidine benzonitrile additive are denser and the surface is smoother than that of the Control group.
[0091] The perovskite film of Example 1 was tested by scanning electron microscope at the buried interface. The results are as follows: Figure 7-2 ,It can be seen from the figure that the holes at the buried ,interface are reduced.
[0092] The space charge limited current test was performed on the perovskite solar cell (FTO / TiO2 / BG / perovskite absorber layer / PCBM / Ag) with the addition of guanidine benzonitrile (BG) additive in Example 1, and the result was Figure 8-2 , where V TFL is the full trap limit voltage, according to V TFL The formula V TFL =
[0093] E trap L 2 / 2ε0εCalculate the defect state density N trap ,pass Figure 8-2 It can be found that the two-dimensional ACI perovskite solar cell with the addition of guanidine benzonitrile BG has a smaller V TFL , then the two-dimensional ACI-type perovskite solar cells with the addition of guanidine benzonitrile BG additive have a smaller defect density.
[0094] The dark current density-voltage curve of the perovskite solar cell with the addition of guanidine benzonitrile (BG) additive of Example 1 was tested to detect the leakage current of the perovskite solar cell. The test results are shown in Fig. 9 ;pass Fig. 9 It can be seen that the leakage current of the perovskite solar cell with the addition of p-guanidinobenzonitrile (BG) additive is lower than that of the perovskite solar cell of the comparative example.
[0095] Example 2
[0096] According to the method of the present invention, a two-dimensional ACI type perovskite solar cell with a dicyandiamide additive is prepared. The specific steps are the same as those in Example 1, except that the additives spin-coated on the electron transport layer are different. The molecular structure of dicyandiamide is as follows: Figure 3-2 As shown, in Example 2, dicyandiamide is dissolved in isopropanol to form a dicyandiamide solution, and then the dicyandiamide solution is spin-coated on the electron transport layer, annealed on a hot plate at 100°C for 5 minutes, and placed at room temperature to obtain a buried interface layer, through which the dicyandiamide additive is added to the electron transport layer. The concentration of the dicyandiamide solution is 6 mg / ml.
[0097] The JV curve test of the two-dimensional ACI type perovskite solar cell of this embodiment 2 is performed to obtain the energy conversion efficiency of the perovskite solar cell of this embodiment 2. The test structure is shown in FIG. Figure 4 (2H2N), through Figure 4 It can be found that the energy conversion efficiency of perovskite solar cells with the addition of dicyandiamide additive molecules is improved.
[0098] The two-dimensional ACI type perovskite film of this embodiment 2 was subjected to XRD test, and the test results are shown in Figure 5 (2H2N), through Figure 5 It can be found that the peak intensity corresponding to the perovskite with the addition of dicyandiamide additive is improved compared with the perovskite film of the comparative example. Therefore, the perovskite with the addition of dicyandiamide additive has better crystallinity.
[0099] The perovskite film of Example 2 was tested by scanning electron microscopy to characterize the morphological changes of the perovskite film. The test structure is shown in FIG. Figure 6-3 , Figure 6-6 and Figure 7-3 .from Figure 6-3 and Figure 6-6 It can be seen that the grains of the perovskite film with dicyandiamide additive are more compact and the surface is smoother than that of the perovskite film of the comparative example. Figure 7-3 It can be seen that the holes at the buried interface of the perovskite film with the addition of dicyandiamide additive are reduced.
[0100] The space charge limited current test was performed on the perovskite solar cell (FTO / TiO2 / 2H2N / perovskite absorber layer / PCBM / Ag) with the dicyandiamide additive (2H2N) of Example 2. The results are shown in Figure 8-3 (2H2N), where V TFL is the full trap limit voltage, according to V TFL The formula V TFL =eN trap L 2 / 2ε0εCalculate the defect state density N trap ,pass Figure 8-3 It can be found that the perovskite solar cell with the addition of 2H2N has a smaller V TFL , then the perovskite solar cells with dicyandiamide additive have a smaller defect density.
[0101] The dark current density-voltage curve of the perovskite solar cell with the dicyandiamide additive (2H2N) of Example 2 was tested. The test results are shown in Fig. 9 , to detect the leakage current of perovskite solar cells, through Fig. 9 It can be seen that the leakage current of the perovskite solar cell with the addition of dicyandiamide additive is lower than that of the perovskite solar cell of the comparative example.
[0102] The embodiments of the present disclosure have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and variations will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.
Claims
1. A two-dimensional ACI-type perovskite film, characterized in that: The molecular structure of the film is: A’A n B n X 3n+1 ; Where: A' is a guanidine ion, A is one or more of methylamine, formamidine or cesium ion, and B is Pb 2+ and / or Sn 2+ , X is Cl - Br - ,I - One or more of, n is the number of inorganic layers.
2. The two-dimensional ACI-type perovskite film according to claim 1, characterized in that: The film is composed of a buried interface layer coated on an electron transport layer and a two-dimensional perovskite light absorption layer coated on the buried interface layer; The buried interface layer is a spin-coated film of a guanidine derivative solution.
3. The two-dimensional ACI-type perovskite film according to claim 2, characterized in that: The guanidine derivative is p-guanidine benzonitrile or dicyandiamide; The guanidine derivative solution is obtained by dissolving the p-guanidine benzonitrile or the dicyandiamide in N,N-dimethylformamide, isopropanol or ethyl acetate.
4. The two-dimensional ACI-type perovskite film according to claim 3, characterized in that: The concentration of the guanidine derivative solution is 1-10 mg / ml.
5. A two-dimensional ACI-type perovskite solar cell, characterized in that: include: An electron transport layer on the surface of a conductive substrate; A buried interface layer and a perovskite light absorption layer are arranged on the electron transport layer; The two-dimensional ACI-type perovskite film described in any one of claims 1 to 4 is used as the buried interface layer and the perovskite light absorbing layer.
6. The two-dimensional ACI-type perovskite solar cell according to claim 5, characterized in that: A hole transport layer and a top electrode are sequentially arranged on the perovskite light absorbing layer.
7. The two-dimensional ACI-type perovskite solar cell according to claim 6, characterized in that: The conductive substrate is a transparent conductive substrate, and the transparent conductive substrate is a glass substrate, a quartz substrate, a PET plastic substrate, a PEN plastic substrate or a PI plastic substrate; and / or, The electron transport material of the electron transport layer is TiO2, SnO2 or ZnO.
8. The two-dimensional ACI-type perovskite solar cell according to claim 7, characterized in that: The electron transport layer is formed by an indium tin oxide, a fluorine-doped tin dioxide or a grid silver film prepared on the conductive substrate.
9. The method for preparing a two-dimensional ACI-type perovskite solar cell according to any one of claims 5 to 8, characterized in that: include: After preparing the electron transport layer on the conductive substrate, the substrate was transferred to a glove box filled with N2, and the guanidine derivative solution was spin-coated on the electron transport layer, annealed on a hot plate at 80-100°C for 5-10 minutes, and allowed to cool to room temperature to obtain an electron transport layer modified with the guanidine derivative.
10. The method for preparing a two-dimensional ACI type perovskite solar cell according to claim 9, characterized in that: After spin coating a two-dimensional perovskite light absorbing layer on the guanidine derivative-modified electron transport layer, spin coating a Spiro-OMeTAD hole transport layer on the perovskite light absorbing layer, and vapor-depositing an Ag top electrode on the hole transport layer.
